Analisis Faktor Risiko yang Berhubungan dengan Gangguan Elektrolit (Kalium, Natrium, Klorida) pada Pasien Tuberkulosis Paru - Cipta Sari, Dyah Rahajeng; Aktifah, Nurul; Mustikawati, Neti (Universitas Muhammadiyah Pekajangan Pekalongan, 2025)
Pulmonary tuberculosis (TB) can potentially trigger electrolyte disorders. Factors that influence electrolyte disorders include stress, body mass index (BMI), age, and TB treatment. This study aims to determine the risk factors associated with electrolyte disorders (potassium, sodium, chloride) in pulmonary tuberculosis patients. This study used an analytical survey method with data collection using convenience sampling techniques. The sample consisted of 82 pulmonary TB patients who were hospitalized at RSIP Muhammadiyah Pekajangan Pekalongan in July 2024. Data analysis used the chi square test. The results showed that 87.8% of respondents experienced electrolyte disorders, with moderate stress levels of 86.6%, normal BMI of 65.9%, age range ≥60 years of 57.3%, and those not undergoing TB treatment of 78%. There is no relationship between risk factors for stress, body mass index, age, and TB treatment with electrolyte disorders in pulmonary tuberculosis patients. This study suggests that nurses provide education on foods high in potassium, sodium, and chloride to increase patient electrolytes.